Pemberdayaan Petani Salak: Strategi dalam Meningkatkan Pengembangan Ekonomi Lokal di Kelurahan Bobo Kecamatan Tidore Utara Kota Tidore Kepulauan - Zuleiha Husen; Nurlaila Nurlaila; Zandy Pratama Zain; Abdul Bahar Muslim (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Snake Fruit or Salak is a commodity that is quite in demand by the community. Currently, the products that can be enjoyed are fruit and juice. Meanwhile, the potential for processing other products is still lacking to be explored to provide benefits for producers. Therefore, our team held a workshop that focused on the production of snake fruit products. This workshop aims to equip local residents with the knowledge and skills to utilize snake fruit, a resource that is widely available but potentially underutilized in the community. This workshop consists of a tutorial on processing snake fruit into various products. We provide participants with hands-on experience and guidance on making items such as jam, jelly, or even dried snake fruit snacks. Two weeks after the workshop, a follow-up evaluation was conducted to assess the effectiveness of the training and explore potential challenges faced by participants in applying their new skills. The contribution of this project is the empowerment of the Bobo Village community through knowledge sharing and promoting the use of local resources in the form of Snake Fruit Dates and Sweetened Snake Fruit